DEKONSTRUKSI MAIN COURSE DAGING ASAP HOTEL DE BRAGA - Nikolas Antoni C.S (LPSDI Bina Patria, 2024)
Bandung is renowned for its rich culinary landscape and food innovations. A notable recent development at Hotel De Braga is the deconstructed main course served at B10 Restaurant. This menu item reinterprets traditional dishes into a new form, presenting sushi filled with smoked meat and cassava leaves. The observed decline in sushi consumption is attributed to issues with flavor and affordability. De Braga’s innovation aims to boost sushi consumption by adapting it to Indonesian tastes, specifically by replacing traditional sushi fillings with smoked meat and cassava leaves.